Joint engagement is a potential mechanism leading to increased initiations of joint attention and downstream effects on language: JASPER early intervention for children with ASD. (25th March 2021) - Shih, Wendy; Shire, Stephanie; Chang, Ya‐Chih; Kasari, Connie
Abstract : Background: Social communication interventions benefit children with ASD in early childhood. However, the mechanisms behind such interventions have not been rigorously explored. This study examines the mechanism underlying a naturalistic developmental behavioral intervention, JASPER (Joint Attention, Symbolic Play, Engagement, and Regulation), delivered by educators in the community. Specifically, the analyses focus on the mediating effect of joint engagement on children's initiations of joint attention (IJA) skills and whether IJA postintervention are associated with later gains in children's receptive and expressive language. Methods: One hundred seventy‐nine children, age 2–5 years, were randomized to immediate JASPER treatment or waitlist (treatment as usual) control. Independent assessors blinded to time and treatment coded children's time jointly engaged and IJA during a 10‐min teacher–child interaction at baseline, exit, and follow‐up. Age‐equivalent receptive and expressive language scores from the Mullen Scales of Early Learning were collected at baseline and follow‐up. Mediation analyses with linear mixed models were used to explore the potential mediating effect of joint engagement on IJA. Results: Joint engagement significantly mediated 69% of the intervention effect on young children's IJA and IJA predicted improvements in standardized language scores. Conclusions: Small but sustained changes in child‐initiated joint engagement improved IJA, a core challenge in children with ASD, which in turn led to improvements in language.